Peran Influencer Media Sosial, Ulasan Pelanggan dan Kualitas Produk Terhadap Keputusan Pembelian Pada Brand Eiger (Studi Mahasiswa Universitas Islam Malang FEB Angkatan 2021) - Nayif Syihab, Achmad Hisyam; Basalamah, Muhammad Ridwan; Mahardani, Ahmad Subhan (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to examine the influence of social media influencers, customer reviews, and product quality on purchasing decisions for the Eiger brand. Utilizing a quantitative approach, data were collected through questionnaires from 100 respondents—students of the Faculty of Economics and Business, Islamic University of Malang, class of 2021—and analyzed using SPSS version 27 through validity and reliability testing, classical assumption tests, and multiple linear regression analysis. The results show that all three independent variables, namely influencer role, customer reviews, and product quality, have a significant effect on purchasing decisions, both partially and simultaneously. The Adjusted R² value of 0.734 indicates that the model explains 73.4% of the variance in consumers' purchasing decisions regarding Eiger products. These findings highlight the importance of effective digital marketing strategies through influencer collaboration, proper customer review management, and continuous product quality improvement in driving consumer buying interest, particularly among the younger generation. Keywords: Social Media Influencers, Customer Reviews, Product Quality, Purchase Decision, Eiger